2013
DOI: 10.1155/2013/597461
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Heuristic Based on Clustering Approach for OLSR

Abstract: Due to the dynamic nature of mobile ad hoc network (MANET), the quality of service (QoS) requires several improvements. The present papercomeswithin the framework of research to optimize QoS in MANET. In this paper, we propose a novel version of OLSR based on the clustering approach which is inspired from Lin and Chu heuristic and adapted to beimplemented inOLSR. We studied its stability and we compared its performances to those of standard OLSR. The metrics we used in evaluating network performances were aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, the evaluations did not consider the case where a mesh-like clustering scheme such as MPR would operate only using road traffic direction. In low-mobility MANETs (up to 10 m/s), the authors of [21] showed that an OLSRbased clustering approach, even with overlapping clusters, can help reduce end-to-end delay and routing traffic overhead. The authors did not conduct any comparison with a backbone-like clustering scheme.…”
Section: Related Workmentioning
confidence: 99%
“…However, the evaluations did not consider the case where a mesh-like clustering scheme such as MPR would operate only using road traffic direction. In low-mobility MANETs (up to 10 m/s), the authors of [21] showed that an OLSRbased clustering approach, even with overlapping clusters, can help reduce end-to-end delay and routing traffic overhead. The authors did not conduct any comparison with a backbone-like clustering scheme.…”
Section: Related Workmentioning
confidence: 99%
“…This is shown in Figure 10 , which shows that the remaining liveliness in this situation is adequate until the death of the final node [ 37 ].…”
Section: Proposed Energy Protocol With Blockchainmentioning
confidence: 99%
“…This approach is proposed to reduce the storage and processing information within a cluster. In the literature we can have several clustering techniques; the K-means clustering technique is among the best methods known [11,12] used in MANETs. This one will allow clusters to be more stable and the center will be better chosen.…”
Section: Problem Formulationmentioning
confidence: 99%